Pond Fish Farming under NGO Support and Individual Management: A Comparative Socioeconomic Study (The Agriculturists, 2014)
The study was conducted to compare the profitability of fish farming under NGO support and individual management and to evaluate the overall impact of NGO intervention on farmers income. A total of 120 farmers (60 for own management and 60 for NGO support) were selected following random sampling technique for data collection from both Mymensingh and Tangail District. The data were collected through direct interview from the selected fish farmers. Data were analyzed with a combination of tabular and functional analysis. The BCR was 1.9 for own management and 2.4 for NGO supported pond fish farming which shows that the fish farming is more profitable under NGO support. The Ravallion test results showed that the income was increased by the amount of Tk. 32500 due to NGOs intervention. Cobb-Douglas production function analysis was done to determine the effects of variables on pond fish production. Out of six variables, three variables in case of own management and four variables in case of NGO support had significant impact on per acre output of fish production. The results of the efficiency computation indicated that labour, feed and lime and medicine were being underutilized and fingerlings and irrigation were being over utilized for own managed pond. Under NGO supported pond, labour, fingerlings and lime and medicine were being underutilized and feed and irrigation were being over utilized. DOI: http://dx.doi.org/10.3329/agric.v12i1.19584 The Agriculturists 2014; 12(1) 75-84